2016
DOI: 10.1149/2.0651606jes
|View full text |Cite
|
Sign up to set email alerts
|

An Effective, Point-of-Use Water Disinfection Device Using Immobilized Black TiO2Nanotubes as an Electrocatalyst

Abstract: The following study characterized titanium dioxide nanotube arrays (TNAs) annealed in air (air-TNA), nitrogen (N2-TNA) or hydrogen with a nitrogen balance (H2-TNA) for the rapid disinfection of waterborne bacteria. The H2-TNA became black after annealing due to a large concentration of oxygen vacancies, leading to a higher absorbance in the visible light region compared to the air-TNA and N2-TNA. Photoelectrochemical testing showed that the N2-TNA had the highest photocurrent response in the absence of an appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…The anodic formation of the TiO 2 -NT arrays are described in detail in our earlier work (Carlson et al [5]); however, the following is an overview of the process. A titanium wire coil (ESPI metals, 99% purity) was used for the degradation array (DA) and titanium foil (ESPI metals, 99% purity) was used for the sensor array (SA).…”
Section: Formation Of the Titanium Dioxide Nanotube-based Arraysmentioning
confidence: 99%
See 3 more Smart Citations
“…The anodic formation of the TiO 2 -NT arrays are described in detail in our earlier work (Carlson et al [5]); however, the following is an overview of the process. A titanium wire coil (ESPI metals, 99% purity) was used for the degradation array (DA) and titanium foil (ESPI metals, 99% purity) was used for the sensor array (SA).…”
Section: Formation Of the Titanium Dioxide Nanotube-based Arraysmentioning
confidence: 99%
“…Carlson et al [5] demonstrated that annealing TiO 2 -NTs in a reducing atmosphere creates such a high concentration of defects that oxidizing species can be generated in the absence of UV irradiation using only an applied bias. This technique was utilized for the inactivation of bacteria in a multi-channel flow reactor where +6 V was applied to the DA to produce the maximum radical generation without causing physical damage to the NTs.…”
Section: Radical Formation and Optimizationmentioning
confidence: 99%
See 2 more Smart Citations
“…The novel focus of this paper is to demonstrate that the electrochemical sensor could be paired with ER sterilization. The disinfection system consists of a defect laden titania nanotube-based reactor that physically destroys waterborne pathogens via the electrocatalytic generation of oxidizing radicals [ 14 , 15 , 16 ]. Cell death occurs in this electrocatalytic reactor (ER) via interaction with oxidizing radical species formed on the surface of the titania anode.…”
Section: Introductionmentioning
confidence: 99%